(3GdYTbs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3HYO GdHSedI hGdOjHGLI SCdJ Cf CML dc QSGdI ef EjVGM Gdbhd ai GdYTb Ydi SHjd GdEjLGR aCLHJ GdaUd GdChd ai PcQ SQjGf GdYTb ai cd hGMO s
(3BNQgG (B:s
(3aEPf GdNjQ GdeWdb bO jYTb GdMceI Cf JfGd efg fjdkG hEf ce JHdZ ceGd GdOQLI efg s
(3Vef eLehY , JQJjHgG (B: 5s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
Keywords: (3eJaQbGJs